Common and different neural markers in major depression and anxiety disorders: A pilot structural magnetic resonance imaging study. (30th August 2019) - Maggioni, Eleonora; Delvecchio, Giuseppe; Grottaroli, Marika; Garzitto, Marco; Piccin, Sara; Bonivento, Carolina; Maieron, Marta; D'Agostini, Serena; Perna, Giampaolo; Balestrieri, Matteo; Brambilla, Paolo
Highlights: Investigation of cortical morphology in GAD, PD and MDD Shared deficits in PFC may explain the clinical similarities between MDD, PD and GAD Diagnosis-specific deficits in frontotemporal and parietal areas in MDD, PD and GAD Abstract: Although anxiety and depression often co-occur and share some clinical features, it is still unclear if they are neurobiologically distinct or similar processes. In this study, we explored common and specific cortical morphology alterations in depression and anxiety disorders. Magnetic Resonance Imaging data were acquired from 13 Major Depressive Disorder (MDD), 11 Generalized Anxiety Disorder (GAD), 11 Panic Disorder (PD) patients and 21 healthy controls (HC). Regional cortical thickness, surface area (SA), volume and gyrification were measured and compared among groups. We found left orbitofrontal thinning in all patient groups, as well as disease-specific alterations. MDD showed volume deficits in left precentral gyrus compared to all groups, volume and area deficits in right fusiform gyrus compared to GAD and HC. GAD showed lower SA than MDD and PD in right superior parietal cortex, higher gyrification than HC in right frontal gyrus. PD showed higher gyrification in left superior parietal cortex when compared to MDD and higher SA in left postcentral gyrus compared to all groups. Our results suggest that clinical phenotypic similarities between major depression and anxiety disorders might rely on common prefrontal alterations. Frontotemporal and parietal abnormalities may represent unique biological signatures of depression and anxiety.